Crafting Competitive Strategies for Creative Enterprises: Evidence from a SWOT Analysis of Zafirah Giftbox - Jehan Galuh Farwati; Rita Mutiarni (Proceeding International Conference on Digital Education and Social Science, 2025)
Increasing competition in the creative industry requires micro, small, and medium enterprises (MSMEs) to adopt adaptive and evidence-based business development strategies. This study aims to analyze the internal and external conditions of Zafirah Giftbox and to formulate appropriate business development strategies using an integrated SWOT approach. A qualitative descriptive method was employed, with data collected through direct observation, in-depth interviews with the business owner, and documentation. The analysis was conducted using the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal–External (IE) Matrix, and Grand Strategy Matrix. The results indicate that Zafirah Giftbox possesses key strengths in creative design, product personalization, and close customer relationships, while weaknesses remain in digital promotion and marketing management. The IFE and EFE scores place the business in a moderate strategic position, suggesting a hold-and-maintain strategy. Furthermore, the Grand Strategy Matrix highlights market penetration and product differentiation as the most relevant strategic alternatives. These findings emphasize the importance of internal capability strengthening and digital marketing optimization to enhance the competitiveness and sustainability of creative MSMEs.